Metallothioneins Gene Regulation Through Promoter DNA Methylation According to Zn and Cu Trace Elements Status in Human Hepatocellular Carcinoma (P05-002-19). (13th June 2019) - Santis, Domenica De; Udali, Silvia; Mazzi, Filippo; Ruzzenente, Andrea; Beschin, Greta; Pattini, Patrizia; Franceschi, Antonia; Moruzzi, Sara; Guglielmi, Alfredo; Olivieri, Oliviero; Friso, Simonetta; Choi, Sang-Woon
Abstract: Objectives: Hepatocellular carcinoma (HCC) is the most frequent primary liver cancer, yet mechanisms of hepatocarcinogenesis are largely unknown. A particular interest was recently dedicated to the role of trace elements and metallothioneins (MTs), a group of proteins involved in metal ions homeostasis and detoxification, have been suggested as possible tumor suppressor genes. The study of MTs transcriptional regulation by promoter DNA methylation is the object of study as a possible mechanism responsible for gene silencing through epigenetics. Methods: Twenty-seven HCC patients undergoing surgery intervention were enrolled and clinically characterized. MT1G and MT1H gene expression was performed by Real Time qPCR. DNA methylation analysis in 23 HCC and homologous non-neoplastic liver tissue (N) was performed by Bisulfite-Amplicon Sequencing (BSAS) in an overlapping region (∼400 bp) of the promoters of the two genes. Cu and Zn concentrations were measured in serum and liver tissues (HCC and N) by Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Kaplan-Meier analysis of survival was performed according to serum trace elements. Results: MT1G and MT1H were transcriptionally repressed in HCC tissue as compared to N. A correlation was observed between the mRNA levels of the two MTs, in particular MT1G was repressed in 23 out of 27 HCC tissue ( P = 0.0366) and MT1H was repressed in 24 out of 27 HCC tissue ( P = 0.0077). The promoter region resulted hypermethylated in 9 out of 19 HCC that showed MT1G and MT1H down-regulation. Serum Zn and Cu levels were within the normal range while HCC tissue exhibited significantly reduced Zn levels as compared to N ( P < 0.0001). Tissue Cu levels did not show significant differences. Serum trace elements levels were also analyzed according to patients clinical features and those with Cu levels higher than the 75th percentile had a significantly poorer prognosis than those within the lowest Cu levels quartile ( P < 0.05). Conclusions: MT1G and MT1H are repressed in HCC tissue. In a subset of patients the downregulation was associated to promoter hypermethylation, supporting the hypothesis of MT1G and MT1H as possible tumor suppressor genes in HCC. Evidence of a correlation between serum Cu levels and survival rate provide new insights for the role of this microelement in liver carcinogenesis. Funding Sources: No funding sources.